A development of real-Time fetal movement detector - Norasethasopon, Pathara; Chitsakul, Kitiphol; Tretriluxana, Suradej (My University, 2016)
Fetal Movement (FM) is a marker for evaluating wellbeing of the unborn baby. Naturally, pregnant women can sense any movement in her abdomen. However, there are two groups of women who may have degraded this sensing ability. A primigravida, a first time pregnant woman, may not be able to recognize the fetus movement. A working pregnant woman may be too busy to aware of her fetus responses. In this paper, a development of real-Time fetus movement detector is presented. An air pressurized bag is designed to be wrapped around the abdomen of pregnant woman. It is connected to a pressure sensor in order to detect the force exerted against the uterus wall in any direction. The signal is processed before uploaded into internet cloud services for real-Time monitoring and remote access.
Keywords: fetal movement; internet cloud service; intrauterine force-pressure model; pregnancy; real-Time monitoring